A promising strategy for the large-scale preparation of spherical calcium carbonate by efficiently using carbon dioxide. (September 2022) - Ma, Jianping; Ji, Junrong; Yaseen, Muhammad; Chen, Xiaopeng; Liao, Dankui; Tong, Zhangfa
Abstract: Spherical calcium carbonate (CaCO3 ) is widely used in industries. However, its large-scale synthesis still remains a challenging issue. Herein, we report the preparation of spherical CaCO3 at a high calcium hydroxide (Ca(OH)2 ) concentration (1.08 M) using CO2 highly efficiently in methanol (CH3 OH)-water mixed solvent with polyethyleneimine (PEI) as a crystal modifier by carbonation method. Experimental results revealed that the introduction of CH3 OH in the reaction systems decreased the saturation Ca 2+ concentration in the solvent, and then formed spherical CaCO3 under the controlled action of PEI. Besides, spherical CaCO3 with a particle size of about 1 µm can be obtained at concentration of Ca(OH)2 of 1.08 M, PEI of 5 g/L, and CH3 OH volume content of 30%, stirring rate of 450 rpm, and CO2 flow rate of 1.4 m 3 /h. The formation mechanism of spherical CaCO3 indicated that the particles converted from an initial amorphous precursor, to needle-like, bundle-like, block-like and hemispherical shaped aggregates, and finally to a complete spherical CaCO3 morphology. This research provides an effective method for the preparation of high yield spherical CaCO3 by industrial carbonation method. Graphical Abstract: ga1 Highlights: A method for the large-scale preparation of spherical CaCO3 using CO2 highly efficiently was proposed. The role of CH3 OH in the preparation of high yield spherical CaCO3 was demonstrated experimentally. The formation mechanism of spherical CaCO3 was revealed.